Development and Feasibility of a Heyzine Flipbook–Based Tricaka E-Module for Grade VII Students’ Javanese Script Writing Skills - Nihaya Nurjanah; Agus Yuwono (AL-ISHLAH: Jurnal Pendidikan, 2025)
Learning to write Javanese script (hanacaraka) at the junior high school level remains challenging due to low student motivation and limited instructional media that support systematic writing practice. This study aimed to develop and examine the feasibility of a Heyzine Flipbook–based Tricaka e-module designed to support Grade VII students’ Javanese script writing skills. The study employed a Research and Development (RD) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through observations, interviews, and questionnaires, including needs analysis, expert validation instruments, and user response questionnaires. The e-module was validated by a material expert and a media expert and subsequently implemented in a limited trial involving one Javanese language teacher and 32 Grade VII students at SMP Negeri 01 Juwana during the 2024/2025 academic year. Data were analyzed using descriptive statistics in the form of feasibility percentages. The results showed that the e-module achieved a feasibility score of 83.33% from the material expert and 85% from the media expert, both categorized as highly valid. User responses also indicated very high feasibility, with 95% from the teacher and 97.08% from the students. These findings suggest that the Tricaka e-module is feasible for use as a learning medium in Javanese script writing instruction. Further research is recommended to examine its effectiveness in improving students’ writing performance through experimental designs with larger and more diverse samples.